Third‐Degree Atrioventricular Block and Collapse Associated with Eosinophilic Myocarditis in a Horse. (14th March 2017) - Luethy, D.; Slack, J.; Kraus, M.S.; Gelzer, A.R.; Habecker, P.; Johnson, A.L.
Abstract : Third‐degree atrioventricular block (AVB) and primary inflammatory myocarditis are uncommon findings in horses. The horse of this report presented for collapse at rest and was found to have multiple cardiac arrhythmias, most notably 3rd‐degree AVB. The horse was subsequently diagnosed with eosinophilic myocarditis on necropsy, a rare form of myocarditis not previously reported in horses. Despite extensive testing, an etiologic agent could not be identified, illustrating the difficulty in identifying a specific cause of myocarditis in horses.